Pengenalan Budaya Nusantara bagi Anak Migran Indonesia melalui KKN Internasional di At-Tanzil Lembah Jaya 2, Malaysia - Sri Rahayu; Winnantyazka Harliandiva Ambarwati; Dihni Sofwatun Najah (Pusat Riset dan Inovasi Nasional, 2026)
This international collaboration Real Work Lecture (KKN) activity aims to introduce Indonesian cultural values to Indonesian migrant children at the At-Tanzil Lembah Jaya 2 Learning Studio, Malaysia. Nusantara culture has an important role in supporting the formation of children's identity and character, especially for those who live in multicultural environments and are far from the homeland. The implementation of the activity was carried out through a participatory approach with the introduction of folklore, regional songs, and traditional Indonesian arts and games that were adjusted to the age and characteristics of the students. In addition, the activities are also designed interactively so that children can be actively involved in each cultural learning session. The results of the activity showed that the children responded positively and enthusiastically during the activity, as well as experienced an increase in understanding of the values of togetherness, mutual cooperation, tolerance, and love for Indonesian culture. This activity shows that the introduction of archipelago culture can be an effective educational medium in supporting the formation of character, national identity, and a sense of pride as the next generation of the nation for Indonesian migrant children abroad.